Sodarcan : un holding d’assurance et de réassurance - Parizeau, Robert (Assurances)

(untitled) (HEC Montréal, 1994)
Sodarcan inc. marked its twentieth year of incorporation in 1992. Through the years, Sodarcan has remained true to its fundamental commitment to the quality of its services, while adapting to the upheavals that have shaped the insurance industry. ln the following pages, Robert Parizeau, President of Sodarcan, explains why the Group withdrew from insurance and reinsurance underwriting to concentrate on its core operations: insurance brokerage, actuarial services and employee benefits consulting, and reinsurance brokerage–the three sectors of activity in which Sodarcan has earned an increasingly enviable reputation. Dale-Parizeau inc., MLH + A inc. and BEP International inc. are each recognized as key players, if not leaders in their respective fields of activity in Canada, making Sodarcan the largest Canadian-owned insurance intermediary.